2009
DOI: 10.1243/09544119jeim553
|View full text |Cite
|
Sign up to set email alerts
|

Development of a customized density—modulus relationship for use in subject-specific finite element models of the ulna

Abstract: Assigning an appropriate density-modulus relationship is an important factor when applying inhomogeneous material properties to finite element models of bone. The purpose of this study was to develop a customized density-modulus equation for the distal ulna, using beam theory combined with experimental results. Five custom equations of the form E= ap(b) were used to apply material properties to models of eight ulnae. All equations passed through a point (1.85, Ec), where p = 1.85 g/cm3 represents the average d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Density-elasticity relationships have also been developed using optimization techniques for the human femur (8,194,195), tibia (8,196), humerus (8), radius (8), and ulna (197).…”
Section: The Finite Element Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Density-elasticity relationships have also been developed using optimization techniques for the human femur (8,194,195), tibia (8,196), humerus (8), radius (8), and ulna (197).…”
Section: The Finite Element Methodsmentioning
confidence: 99%
“…Such equations have shown that a single equation can be used for both the trabecular and cortical bone (194,195,197). However, the optimized density-elasticity equations still illustrate site-and cohort-specificity (194).…”
Section: The Finite Element Methodsmentioning
confidence: 99%
“…15,17 A custom density-modulus relationship (E ¼ 8346r 1.5 ) was used to apply the tissue properties; this relationship showed lower root mean squared errors to experimental results than previously published relationships when applied to an ulnar model. 17 The Wright implant stem is manufactured of titanium, while the Wright head, SBI stem, and SBI head are made of cobalt chrome (CoCr). The elastic modulus values of titanium, CoCr, and bone cement were set to 110, 214, and 1.95 GPa, respectively.…”
Section: Model Developmentmentioning
confidence: 99%
“…21 The proximal end of the ulna was assumed to be fully fixed. The same coordinate system defined for native models in previous studies 15,17 were used to define the loading direction in the implant models.…”
Section: Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation